Nuclear liability – a comparative assessment of the legal situation in South Africa and Germany against the backdrop of international law - Lang,Tobias Maximilian Hagen (Institute of Marine and Environmental Law, 2019)
The study is concerned with the topic of nuclear liability. One might think this is a topic of the last century, but it is not. In the last few years the demand and development of nuclear power plants were enhanced due to several reasons. Especially in South Africa, the further development of nuclear power plants is planned by the government. However, nuclear energy is an ultra-hazardous energy resource which could cause huge damage to people, their property and the environment. Therefore, a comprehensive legal framework for cases of nuclear damage is needed to balance the interests of victims and the nuclear industry. A legal framework regulating the case of nuclear damage can be found in international law, as well as in most domestic legal systems of countries producing nuclear energy. Due to the fact that South Africa wants to develop its nuclear energy programme, it is interesting to examine its nuclear liability provisions closer. The study assesses the South African nuclear liability regime by comparing it with the international legal framework for nuclear liability and the German nuclear liability regime. Therefore, the study will firstly outline principles of nuclear liability, secondly analyse the most important international conventions and finally examine the crucial nuclear liability provisions in the domestic legal systems of Germany and South Africa.